Application of Problem-Based Learning Model STEM-Based on Biology Lessons for High School Students Communication Skills - Gamar B.N. Shamdas*; Mursito Bialangi; Amalia Buntu; Ihwan Ihwan (Jurnal Pendidikan Sains Indonesia, 2023)
Good quality communication skills are not evenly distributed among students in secondary schools. This quantitative study with a quasi-experimental method aims to describe high school students' communication skills through STEM-based PBL learning in Biology, describe high school students' oral and written communication skills through STEM-based PBL learning in Biology, and describe high school students' communication skills through PBL-based learning and STEM in Biology lessons by gender. The research design is a Posttest Only Control Design carried out on class XI students of SMAN Terpadu Madani Palu with a population of 7 classes totaling 220 students. The research sample used 2 classes totaling 64 students. Determination of the sample by purposive sampling considering the number of students and cognitive abilities of students in 2 classes are homogeneous. Data on written communication skills were obtained through tests using multiple-choice reasoned given during the post-test. Data on oral communication skills were obtained through observation of student activities during the learning process. The results showed that Biology learning by applying STEM-based PBL had a significant effect on the communication skills of high school students compared to direct STEM-based learning, written communication skills were better than oral communication skills and female students' communication skills were significantly better than male students